Design of a Web-based Production and Sales Management Information System for the Small Business Convection Industry - Samuel Ramos (BIOS: Jurnal Informatika dan Sains, 2024)
This research aims to develop a web-based information system to overcome production and sales management problems in the small-scale convection industry. The main problem faced is the lack of efficiency due to manual recording, which causes errors in stock management, ordering, and production. The solution offered is to design an information system with key features such as raw material stock management, customer ordering, production management, and sales reports. The system was developed using the Waterfall method and implemented to optimize production and sales management. The development results show an increase in operational efficiency through real-time stock monitoring, faster order processing, and accurate report generation. System testing ensures that all features function properly and can meet business needs in improving efficiency operationally.